2009
DOI: 10.1901/jaba.2009.42-819
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Utility of a Demand Assessment for Functional Analysis

Abstract: We evaluated the utility of an assessment for identifying tasks for the functional analysis demand condition with 4 individuals who had been diagnosed with autism. During the demand assessment, a therapist presented a variety of tasks, and observers measured problem behavior and compliance to identify demands associated with low levels of compliance or high levels of problem behavior (low-probability demands) and demands associated with high levels of compliance or low levels of problem behavior (high-probabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 8 publications
1
47
0
Order By: Relevance
“…The current evaluation attempted to develop and validate a direct observation method for selecting aversive stimuli for inclusion in the negative reinforcement test condition of an FA, extending findings from previous research (Call et al, , ; Roscoe et al, ). The methodology related to the paired‐stimulus preference assessment for identification of preferred stimuli was applied to the systematic identification of preference for demands (i.e., PSDA).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The current evaluation attempted to develop and validate a direct observation method for selecting aversive stimuli for inclusion in the negative reinforcement test condition of an FA, extending findings from previous research (Call et al, , ; Roscoe et al, ). The methodology related to the paired‐stimulus preference assessment for identification of preferred stimuli was applied to the systematic identification of preference for demands (i.e., PSDA).…”
Section: Discussionmentioning
confidence: 82%
“…Practitioners often rely on unstructured caregiver interviews to identify stimuli included in negative reinforcement test conditions. There are, however, a few notable exceptions, which include the Negative Reinforcement Rating Scale (NRRS; Zarcone, Crosland, Fisher, Worsdell, & Herman, ), a demand analysis using a rate measure (Roscoe, Rooker, Pence, & Longworth, ), and a demand analysis using a latency measure (Call, Pabico, & Lomas, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Data from several studies have indicated that specific antecedent and consequent events may influence the occurrence of problem behavior during an FA, producing both false‐positive (Galiatsatos & Graff, 2003; Shirley et al, 1999) and false‐negative (O'Reilly, Lancioni, King, Lally, & Dhomhnaill, 2000; Roscoe, Carreau, MacDonald, & Pence, 2008; Roscoe, Rooker, Pence, & Longworth, 2009) outcomes. In each case, clarification of results required further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Call et al [23] and Roscoe et al [24] demonstrate the utility of manipulating task-aversiveness in order to reveal a demand escape function to selfinjurious behaviour. These techniques borrow from the principles used in preference assessments by monitoring participant responses to an increasingly aversive hierarchy of demands.…”
Section: Behavioural Assessmentmentioning
confidence: 99%